Eliot’s Modernist Manifesto - Viorica Patea (Transatlantica)
This essay revisits Eliot’s seminal text “Tradition and the Individual Talent” (1919) which has been part of the central debates of literary discussions for almost a century. Although no longer an orthodoxy in our postmodern era, Eliot’s essay continues to influence current critical debates. The goal of this article is to rethink Eliot’s manifesto from the perspective of romantic and modernist poetics, and to reconcile the great disparity between Eliot the experimentalist avant-garde poet who advocates the aesthetics of fragmentation and the critic who pleads for the extinction of personality. This article reconsiders Eliot’s concepts of tradition and impersonality in the light of the revolution that took place in the visual arts in the first decades of the twentieth century, whose experimental language he tried to transfer to poetic practice. It also analyzes the way in which his theories present affinities with modern trends of philosophical thinking, such as historicist hermeneutics, relativism and pragmatism.